Unpacking Digital Public Infrastructures: Foundational Capabilities for Public-Interest Digital Value Creation - Bauer, Luca T.; Degen, Konrad; Schönborn, Sofie; Niehaves, Björn (Conference on Digital Government Research, 2025)
Digital Public Infrastructures (DPIs) are an emerging concept for building foundational digital capabilities—such as digital identity, data sharing, and payments—designed and governed in the public interest to foster generative value creation. Although DPIs are increasingly promoted as instruments for enabling collaboration among governments, citizens, and organizations, the concept remains underdefined in both academic and policy discourse. This study addresses that gap by applying the Technology-Organization-Environment (TOE) framework and a grounded theory approach to analyze 143 academic and non-academic sources published between 2011 and 2024, including work from international organizations, think tanks, and philanthropic entities. We offer three primary contributions: First, we define DPIs as socio-technical systems with modular and layered architectures, governed through public-private collective action to support value creation and multi-actor interaction at scale. Second, we develop a conceptual framework structured around technological, organizational, and environmental dimensions. This framework identifies governance architecture and functional modularity, stakeholder orchestration, and public-private governance, as well as policy context and public rationale, as critical characteristics of emerging DPIs. Third, we position DPIs as an evolution of digital infrastructure and platform models, reoriented toward public interest objectives. We conclude with a call for interdisciplinary research to examine the design, implementation, and governance of DPIs across diverse regional contexts. Emphasizing their potential to deliver inclusive, interoperable, and scalable infrastructure capabilities, we argue that DPIs offer a promising foundation for addressing complex societal challenges